Prevalence, genetic diversity, and molecular detection of the apple hammerhead viroid in Germany - Zikeli, Kerstin; Berwarth, Constanze; Born, Ute; Leible, Thomas; Jelkmann, Wilhelm; Hagemann, Michael Helmut (Frontiers in Microbiology, 2025)
IntroductionApple hammerhead viroid (AHVd) is an emerging plant pathogen infecting apple orchards worldwide. Its genetic variability and geographical distribution remain poorly understood, limiting effective diagnostics and management strategies.MethodsIn this study, 192 samples from German apple orchards were analyzed using reverse transcription (RT) and real-time PCR, one-step RT real-time PCR, and Sanger sequencing. Next-generation sequencing (NGS) was employed on pooled RNA extracts to explore genetic diversity. Phylogenetic relationships were inferred using maximum likelihood methods, and viroid-derived small RNAs (vd-sRNAs) were identified from small RNA sequencing data.Results and discussionAHVd was detected in 78% of samples, with prevalence varying by region: southern (82%), eastern (90%), northern (72%), and western (70%) states of Germany. Phylogenetic analysis revealed distinct clusters linked to geographical origins, indicating isolated evolutionary pathways. NGS analysis uncovered 39% inter-sample variability and 169 polymorphic positions, while Sanger sequencing of RT real-time PCR products derived from the same samples showed only 3% variability, reflecting dominant quasispecies populations. Small RNA analysis mapped 128,388 reads to the AHVd genome, identifying hotspots within and outside the rod-like structure, suggesting structural and regulatory functions of vd-sRNAs. These findings underline AHVd’s genetic diversity. The complex relationship between AHVd genetic variability and symptom expression necessitates the development of highly sensitive diagnostic tools and adaptive management strategies to effectively monitor and control its spread in apple production.